Business interaction and power structures of coastal communities (study in Sendang Biru Malang Indonesia) - Manzilati, Asfi; Efani, Anthon; Kornitasari, Yenny (2018)
The purpose of this research was to identify power structure of business of coastal community in Sendang Biru Malang. This research was important to conduct because the power is one of the media often used by economic actors in capitalizing economic resources. In industry of the coastal society comes the power structure up between employer and fishermen. This appears due to capitalism intervention in fishermen group and contributes to the implication in terms of economy situation of the fishermen only depending on level of employers’ loyalty. Thus, this situation leads them to have no choice unless subject to the boss’ rule. This research used a symbolic interactionism qualitative approach. The results showed that (1) there are two kinds of interactions- land and sea. (2) The highest power structure is at ship manager. This power is formed from the mastery of capital in the coastal community business. (3) The lowest power structure owned by the crew ship of fishermen with lawuhan-sharing income and profit-sharing income only.